If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 23 = 27 Reorder the terms: 23 + X = 27 Solving 23 + X = 27 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + X = 27 + -23 Combine like terms: 23 + -23 = 0 0 + X = 27 + -23 X = 27 + -23 Combine like terms: 27 + -23 = 4 X = 4 Simplifying X = 4
| 5x-(5-x)=7 | | 3x+10y=189 | | (3sinx-2)/(4sin^2x-1)-10 | | 2x+2y=3(2x+3x) | | 1.2x+3.4=2.45x-1.6 | | 8+2(4x+11)=54 | | 8+2(4x*11)=54 | | 2x=2*0.1557 | | (x/2)-(x/5)=1 | | F(x)=7x-3xfind(-2) | | 2x+11=100 | | 7-5x=x | | F(x)=7x-3x | | x+7=7x-17 | | 6x+2-3x=1 | | a+b^3= | | a/4=8=13 | | 2x/0.2-x=7.03 | | (x/2)-(x/5) | | 4x-12=10x | | 2(x+3)-11=x+5 | | 4x3/8 | | 2x+14=3x+2 | | t=2t-3(1-t) | | 4x+28=2x-1 | | a(1-x)=2ax+3-2a | | 4x-28=5x-40 | | 2(3x-5)+7=33 | | 3w-4=17 | | log16x=5/2 | | ax=a-b+bx | | -5(x-2)=40 |